I am sam love is all you need - Nelson, Jessie; Solomon, Richard; Herskovitz, Marshall; Zwick, Edward; Johnson, Kristine; New Line Cinema Corporation; Bedford Falls Productions; Red Fish Blue Fish Films (Firm); New Line Home Entertainment (Firm) ([California] : New Line Home Entertainment, 2002)
Sam Dawson has the mental capacity of a 7-year-old. He works at a Starbucks, is obsessed with the Beatles and has a daughter with a homeless woman who abandons them. As the daughter reaches age 7, Sam's limitations start to become a problem. When the authorities take his daughter away, Sam shames a high-priced lawyer into taking his case pro bono. In the process, he teaches her a great deal about love, and whether it's really all you need.
Originally produced as a motion picture in 2001
Editor, Richard Chew ; music, John Powell ; costume designer, Susie Desanto ; director of photography, Elliot Davis ; production designer, Aaron Osborne
Cast : Sean Penn, Michelle Pfeiffer, Dakota Fanning, Dianne Weist, Richard Schiff, Doug Hutchison, Loretta Devine, Laura Dern
Keywords: People with mental disabilities -- Drama; Custody of children -- Drama